SYNERGY AMONG ACTORS IN COLLABORATIVE GOVERNANCE FOR WILDLIFE CONSERVATION AND STRENGTHENING OF REOG ART - Hilman, Yusuf Adam; Oktaviani, Diah; Okolie, Ugo Chucks (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
The purpose of this study is to find an ideal Collaborative Governance model for the development of nature conservation to conserve green peacocks as a means of supporting the sustainability of Reog Ponorogo art. The research method used is descriptive qualitative, with data collection techniques using interviews and a purposive sampling model. The results of this study show the effectiveness of developing a Collaborative Governance model with a Quadruple Helix type, how the actors are integrated in carrying out activities, starting from pre-negotiation, negotiation stage, to program implementation, which includes dialogue between actors, further building mutual trust and establishing a commitment that became the benchmark for success in the program. The Kampung Merak program aims to ensure the sustainability of cultural activities and the preservation of animal populations. It preserves and increases the population of green peacocks (Pavo Muticus) through community-based breeding, to meet the demand for green peacock feathers to support the cultural art of Reog Ponorogo.